Konteksasi Kepemimpinan pada Lembaga Pendidikan Swasta - M.Azqi Rojabi; Rizal Taupik, Helmi; Ekawati (Jurnal Dirosah Islamiyah, 2024)
This study discusses the context of leadership in private educational institutions as an attempt to understand the dynamics of leadership in the context of independent educational organizations. This study involves an analysis of the factors that influence leadership in private educational institutions, including the role of leaders, characteristics of institutions, and internal and external dynamics that affect organizational performance. Through a qualitative approach, this study explores the perceptions, experiences, and views of stakeholders in the environment of private educational institutions to provide a holistic picture of the leadership context in them. The results of the study are expected to contribute to the development of leadership theory in the context of private educational institutions and provide practical guidance for leaders and managers of private educational institutions in improving the quality of Education.